Morphometric study of Seagrass Enhalus acoroides (Linnaeus f.) Royle, 1839 in Coastal Waters of Budo Village - Leslida, Ayu; Kepel, Rene Ch.; Menajang, Febry S. I.; Kondoy, Khristin F I.; Lumingas, Lawrence J. L.; Mantiri, Rose O. S. E. (Jurnal Ilmiah Platax, 2024)
This research concerns the morphometry of seagrass E. acoroides (Linnaeus) Royle in 1839 in the coastal waters of Budo Village, Wori District, North Minahasa Regency. The existence of seagrass ecosystems in coastal waters is so important that it is necessary to carry out morphometric studies of seagrass, both for scientific purposes and for the sake of knowledge about seagrass itself. This research aims to describe the morphometrics of E. acoroides seagrass on the coast of Budo Village, Wori District, North Minahasa Regency, to compare the morphometrics of E. acoroides seagrass based on sampling stations, and to determine the condition of the aquatic environment (temperature, salinity, pH, substrate). The research location was divided into 3 sampling stations, namely the first mangrove area with 20 individuals, the second seagrass area with 30 individuals, and the third coral reef area with 10 individuals. The sampling process is carried out using a roaming survey method, the sample is washed and put into a plastic sample which will then be measured. The results statistically show that E. acoroides species in the coastal waters of Budo Village at three stations show significant differences in morphometric size, where station three is smaller than stations one and two. Environmental conditions and existing environmental parameters cause this. The condition of the environmental parameters at the three stations is still within safe limits, so it is still good for seagrass growth. Keywords: Seagrass, Enhalus acoroides, Morphometrics, Budo Village Abstrak Penelitian ini mengenai Morfometrik Lamun E. acoroides (Linneaus f.) Royle, 1839 di Perairan Pesisir Desa Budo, Kecamatan Wori, Kabupaten Minahasa Utara. Keberadaan ekosistem lamun di perairan pantai ini sangat penting sehingga perlu adanya kajian mengenai morfometrik lamun, baik untuk kepentingan ilmiah maupun untuk kepentingan pengetahuan tentang lamun itu sendiri. Adapun tujuan dari penelitian ini yaitu Mendeskripsikan morfometrik dari lamun E. acoroides di pesisir pantai Desa Budo, Kecamatan Wori, Kabupaten Minahasa Utara, Membandingkan morfometrik lamun E. acoroides berdasarkan stasiun pengambilan sampel,dan Mengetahui kondisi lingkungan perairan (suhu, salinitas, pH, substrat). Lokasi penelitian dibagi 3 stasiun untuk pengambilan sampel yaitu stasiun satu daerah mangrove dengan mengambil 20 individu, stasiun dua daerah lamun 30 individu, dan stasiun tiga daerah terumbu karang dengan mengambil 10 individu. Proses pengambilan sampel dilakukan dengan metode survei jelajah, sampel dicuci dan dimasukkan ke dalam plastik sampel yang kemudian akan diukur. Hasil yang diperoleh secara statistik bahwa spesies Enhalus acoroides di Pesisir Pantai Desa Budo pada tiga stasiun terlihat ada perbedaan nyata untuk ukuran morfometriknya, dimana stasiun tiga ukurannya lebih kecil dibanding stasiun satu dan dua. Hal ini karena kondisi lingkungan dan parameter lingkungan yang ada. Kondisi parameter lingkungan pada tiga stasiun masih dalam batas aman dimana masih baik untuk pertumbuhan lamun. Kata Kunci : Lamun, Morfometrik, Enhalus acoroides, Desa Budo